2,5-Dihydroxybenzaldehyde 4-methylthiosemicarbazone - Tan, Kong Wai; Ng, S.W.; Maah, Mohd Jamil; Ng, C.H. (International Union of Crystallography, 2008)
The planar molecules of the title compound, C9H11N3O2S, are linked into a supramolecualr chain via O-H center dot center dot center dot S hydrogen bonds. These chains are connected into a two-dimensional array via N-H center dot center dot center dot O hydrogen bonds; an intramolecular O-H center dot center dot center dot N hydrogen bond is also present.